Keratoacanthoma of the Nasal Septum Secondary to Ranibizumab Use - Jason E. Cohn; Hilary M. Caruso Sales; Giang Huong Nguyen; Harvey Spector; Kenneth Briskin (Case Reports in Pathology)
Keratoacanthoma (KA) is a benign epithelial tumor that typically presents as a firm, cone-shaped, flesh-colored nodule with a central horn-filled crater. KA is considered to be a low-grade variant of squamous cell carcinoma (SCC). We report a rare case of a 72-year-old male who presented with a KA involving the nasal septum, possibly related to ranibizumab use. A flesh-colored lesion on the right anterior nasal septum lesion was visualized on examination. Histologic examination revealed a well-circumscribed, dome-shaped central crater filled with keratin, well-differentiated squamous epithelium with ground-glass cytoplasm with pushing margins, and intraepithelial microabscesses establishing the diagnosis of KA. KA of the nasal septum has only been reported once in the literature. This case is unusual because it normally presents on sun-exposed areas. Additionally, this patient was taking ranibizumab, a vascular endothelial growth factor (VEGF) inhibitor for macular degeneration. Despite ranibizumab not being directly linked to precancerous and cancerous skin lesions, agents in this medication class have been. Although it is difficult to prove associations in this isolated case, the role of ranibizumab causing cutaneous lesions should be further investigated.